A Critical Analysis on Charkokta Sutikagara in Comparison to Modern Labor Room (AYUSHDHARA, 2024)
Sutikagara refers to a specially designed room for a pregnant woman who is about to deliver a baby in few months. This room is a place for residence of a woman a few days before labour, during labor (Prasava kala) and few days after labor (Sutika kala). In Ayurveda, Acharya Charaka in Shareerasthana 8 has paid detailed attention to its structure (Nirmaan vidhi), facilities (Upkarana) and other relevant details as Pravesha vidhi. Modern labor rooms are designed based on certain guidelines on upgradation of labor rooms which includes constructing new or reorganising the existing labor rooms. They are standardized for delivering high quality services during childbirth. Both Sutikagara and labor room aim to create a safe environment for childbirth but they embody fundamentally different philosophies.